Supersemar dan Stabilitas Politik: Analisis Transformasi Kekuasaan dari Soekarno ke Soeharto Berdasarkan Perspektif Samuel P. Huntington - Naufal, Defa Akhdan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Supersemar, as a historical event, marked the transition of power from President Soekarno to Soeharto, with profound implications for Indonesia's political stability. This study examines the dynamics of power transformation using Samuel P. Huntington's theory of political stability, emphasizing the necessity of robust institutions to accommodate societal changes. It finds that Soeharto's measures, such as the dissolution of PKI and political restructuring, created temporary stability through military dominance but restricted public participation, leading to a long-term legitimacy crisis. Indonesia's experience highlights Huntington's theory's relevance in understanding the tension between stability and political participation in developing nations.